DE-INSTITUTIONALISATION OF CHILD FOSTER CARE SYSTEM IN LITHUANIA: WILL THE “CARRIAGE” MOVE FORWARD? - GVALDAITĖ, Lijana; ŠIMKONYTĖ, Sandra (Socialinė teorija, empirija, politika ir praktika, 2016)
The reform of Child foster care system has recently been one of the priority areas of Lithuanian Social Policy. This process began in our country more than ten years ago following the adoption of the relevant legislation and was largely influenced by the Ratification of the United Nations Convention on the Rights of the Child (1993) and by country’s membership in the European Union (since 2004). However, this process is found to be too inefficient and slow. In spite of some positive developments in the area, each year a large number of children - more than two thousand - are still deprived of parental care, and at the end of the year there are almost ten thousand of them in such situation (which amounts to 2 percent of all children living in Lithuania). Almost half of these children are provided with institutional care, other children are fostered in families (the vast majority of whom are relatives) and only a small part – in family communities. Researchers, social policy experts and representatives of institutions have been expressing criticism towards institutional care for several years. Although international and national laws state that institutional care may only be established for a child as a last resort after all possibilities to accommodate the child in a foster family have been exhausted, statistics show that in many cases because of the underdeveloped system of family foster care and lack of alternative forms of help, the accommodation of a child in a boarding institution is the first and unique means (according to the statistics, in 2014 40% of children were housed in institutions). It is known that the majority of Lithuanian children’s boarding institutions are not suitable for positive child socialisation, not because of material conditions (a large part of the institutions have been restructured), but mainly due to the fact that these structures cannot provide a close family environment, nor they are able to meet the needs of a child in fulfilling relationships with adults. Recent studies have demonstrated that the intellectual and psychical development of children living in boarding institutions slowed down not insomuch due to congenital factors or central nervous system damage, but to the quality of relations and the lack of efficient interaction with adults. The accommodation, supervision and certain security are ensured for the children but they are not protected from mental deprivation that continues in other forms. The researchers point out that attachment disorders and conditions of care at home can cause a variety of children’s health, cognitive, emotional, moral sphere issues (Browne, 2009, Wheten, Osterman 2014). Although a lot of attention in Lithuania is drawn to a child foster care, the amount of research on this topic is not numerous, especially regarding the topic of de-institutionalisation process. Most scientists explored the institutional child care characteristics and the impact on child development and socialisation. Žalimienė (2007) conducted institutional child care quality research, Zbarauskaitė (2012), Lesinkienė and Karalienė (2008) et al. conducted studies on children living in residential institutions in the light of the attachment theory. These revealed the negative impact of institutions on child’s psychosocial development, possible behavioural and emotional problems. Snieškienė and Tamutienė (2014) did the comparative analysis of different forms of childcare from the point of view of human rights – they compared children living in the institutions and in foster families. The study reported that the implementation of indicators of children’s rights are more favourable in the case of family foster care, besides, children experience fewer socialisation problems and are more likely to positively evaluate their living environment and relationships with adults than those living in boarding institutions. Vitkauskas (2010) also examined the child fostering problems from the child protection perspective. Poviliūnas (2014) who has investigated enforcement of child’s welfare policy in Lithuania, argues that it is necessary to speed up the process of de-institutionalisation, and to ensure individualisation of each step, taking into consideration specific interests, needs of each child and other circumstances. Bobinienė and Voitechovič (2012) described possible prevention and intervention measures of child care de-institutionalisation and emphasised the importance of social work with social risk families. Preventive work with families is also highlighted by Pūras (2012) and other authors. This paper analyses current situation of de-institutionalisation of children’s boarding institutions that has started a few years ago in Lithuania, as well as the position, preparation and participation of social workers of those institutions in this process; an example of those who already work in new circumstances is presented as a good practice. The following methods of research have been used: the analysis of the literature, the analysis of legislation, interviews with experts. The purpose of empirical research (interview) was to identify the position of social workers working in children’s boarding institutions, their preparation for de-institutionalisation and participation in the process. To this end, narrative interviews with seven experts from four different children’s boarding institutions were conducted, namely: two institutions in big cities that are similar in the number of accommodated children and in principles of work organisation, one institution in a small town, and one children’s boarding institution where the de-institutionalisation had already started. The interviews and analysis were carried out according to the Grounded theory methodology – Strauss, Corbin version (2008). Several experiences and insights expressed by the interviewees are summarised in this paper and, despite the limitations of the study, results reflect certain trends significant to this process. Of course, a more detailed examination of the situation requires further research. The analysis of academic literature, research, and legislation revealed that de-institutionalisation of children’s boarding institutions is a complex and gradual process that involves not only the shutdown of stationary institutions, but also requires the establishment of alternative help services, development of preventive work with families in order to reduce the number of children getting into the foster care system. Therefore, incompetent and unprepared actions may bring risks to the children in question: they can be forcibly sent back to live in their own problematic families or held up with them, mechanically transferred to other places of residence, regardless of their actual situation, needs and best interests. On the other hand, it is observed that in Lithuania the de-institutionalisation process is too slow and inefficient. Although the reform process was initiated more than ten years ago, there are still some problematic points: no adequate legal framework, lack of clear and unified “Action Plan” to be implemented in different regions, there is no clear financial mechanism. Moreover, the plan to reduce young children’s accommodation in institutions and to decrease the number of social risk families and their children failed; there is still shortage of social services for families, there is no legal regulation of help for a family in a situation of crisis (currently only families included in the Social Risk Record can receive help), etc. The expert interviews showed that professionals lack information and discussions on the topic of de-institutionalisation within boarding institutions, with external experts as well as representatives of responsible authorities. On the other hand, no initiatives from the informants themselves were observed. Ignorance increases anxiety among workers: they raise questions and doubts about the reform process, they remember unsuccessful projects, worry about their jobs or changes in duties. For this reason, it seems that social workers are skeptical about the de-institutionalisation and even oppose it. Hence, all the informants have confirmed that this reform is necessary because the institutions are not equal to family environment and do not correspond to the needs of children. Furthermore, we have seen that those, who have a strong motivation to work with children, are willing to continue their work under new conditions, and those who have weak motivation have more doubts and are not sure that they will conform to the new system. The research highlighted most important factors that could lead to a successful implementation of the reform: dissemination of information, adequate professional training/retraining of specialists, increasing of social workers’ salaries and financial resources in general, analysis of foreign experiences, preparation of detailed projects, oriented to the needs of children and promotion of a coherent preventive work with families. To sum up, it can be said that attempts to reform the child foster care system in Lithuania have indeed been considerable. However, programs, regulations, concepts, strategies have so far been viewed as recommendations and up to now there have been relatively few real steps to reform the existing arrangements. According to the analysed material, it can be deduced that the de-institutionalisation process lacks political will and the unitary participation of all subjects involved and finally that of the entire society. That is why one gets the impression that, like in the fable of S. Krylov, the “carriage” does not start moving. Hopefully representatives of the academic community will get more and more involved in this process with research and scientific insights, recommendations, texts and curricula of the teaching programs, etc.